(untitled) (Forum Penelitian Agro Ekonomi, 2024)
The concept of food sovereignty officially becomes an objective and an approach in national food development such as depicted in Law No. 18/2012 on Food along with food self-sufficiency and food security. However, up to now formulation and understanding of food sovereignty is various and unclear. This article aims to review the concept of food sovereignty at international and national levels. Food sovereignty is a strategy to improve food security as the ultimate goal of food development because the concept is in fact consistent and complementary. Food sovereignty is related with farmers’ rights and access to the entire agricultural resources including land, water, production factors, technology, and marketing as well as on consumption. This condition is measurable at various levels at individual, household, community, regional, and national levels.